Distinct Roles of LFA-1 and ICAM-1 on ILC2s Control Lung Infiltration, Effector Functions, and Development of Airway Hyperreactivity - Hurrell, Benjamin P.; Howard, Emily; Galle-Treger, Lauriane; Helou, Doumet Georges; Shafiei-Jahani, Pedram; Painter, Jacob D.; Akbari, Omid (Frontiers in Immunology, 2020)
Asthma is a heterogeneous airway inflammatory disease characterized by increased airway hyperreactivity (AHR) to specific and unspecific stimuli. Group 2 innate lymphoid cells (ILC2)s are type-2 cytokine secreting cells capable of inducing eosinophilic lung inflammation and AHR independent of adaptive immunity. Remarkably, reports show that ILC2s are increased in the blood of human asthmatics as compared to healthy donors. Nevertheless, whether ILC2 expression of adhesion molecules regulates ILC2 trafficking remains unknown. Our results show that IL-33-activated ILC2s not only express LFA-1 but also strikingly LFA-1 ligand ICAM-1. Both LFA-1−/− and ICAM-1−/− mice developed attenuated AHR in response to IL-33 intranasal challenge, associated with a lower airway inflammation and less lung ILC2 accumulation compared to controls. Our mixed bone marrow chimera studies however revealed that ILC2 expression of LFA-1 — but not ICAM-1 — was required for their accumulation in the inflamed lungs. Importantly, we found that LFA-1 remarkably controlled ILC2 homing to the lungs, suggesting that LFA-1 is involved in ILC2 trafficking to the lungs. Our exploratory transcriptomic analysis further revealed that ICAM-1 deficiency on ILC2s significantly affects their effector functions. While it downregulated pro-inflammatory cytokines such as Il5, Il9, Il13, and Csf2, it however notably also upregulated cytokines including Il10 both at the transcriptomic and protein levels. These findings provide novel avenues for future investigations, as modulation of LFA-1 and/or ICAM-1 represents an unappreciated regulatory mechanism for ILC2 trafficking and cytokine production respectively, potentially serving as therapeutic target for ILC2-dependent diseases such as allergic asthma.